Diversity and distribution of coral gall crabs associated with Red Sea mesophotic corals - Vimercati, Silvia; Terraneo, Tullia I.; Marchese, Fabio; Eweida, Ameer A.; Rodrigue, Mattie; Pieribone, Vincent; Qurban, Mohammed; Duarte, Carlos M.; Benzoni, Francesca (Frontiers in Marine Science, 2024)
Coral-dwelling gall crabs (Cryptochiridae) live in an obligate symbiosis with reef-building corals from shallow to deep waters. In particular, crabs of the genus Opecarcinus are known to occur across the tropical belt in association with the scleractinian family Agariciidae, down to a depth of 89 m. The Red Sea is a semi-enclosed basin that has long been recognized as a region of high marine biodiversity and endemism, with more than 230 decapod species recorded so far. There, nine Opecarcinus species are recorded from shallow and mesophotic corals. However, the occurrence of Opecarcinus below 30 m depth is documented only in the Saudi Arabian coast of the Northern Red Sea, and the rest of the Saudi Arabian Red Sea has remained unstudied. In this work, we assess the diversity and distribution of Opecarcinus from the mesophotic waters of the Saudi Arabian Red Sea. Through Remotely Operated Vehicles (ROV) and Submarines explorations, we collected 10 gall crab specimens associated with Agariciidae corals at mesophotic depths between 47 and 89 m. Two mitochondrial and one nuclear markers were used to obtain crab phylogenetic tree showing that three of the Opecarcinus species known from Red Sea shallow-water corals can also live at mesophotic depths. This is the first assessment of the depth distribution of the genus Opecarcinus in the Red Sea. It provides further evidence of the depth range adaptability of the Opecarcinus-Agariciidae association and highlights the need for a more in-depth investigation of the largely overlooked mesophotic coral-associated fauna.